Analysis of tag recognition ranges and rates according to reader transmission power levels when tracking machines by RFID in underground mines: an indoor experiment. Issue 2 (4th March 2017) - Jung, Jihoo; Choi, Yosoon
Abstract: The objective of this study is to use indoor tests to quantitatively analyze how Radio Frequency Identification (RFID) reader transmission power levels affect tag recognition range and rate when tracking machine locations using an RFID system in an underground mine. We installed an RFID reader and antennas in an indoor testing site that simulates an underground mine drift and operated unmanned autonomous cars with tags attached to them. The tag recognition range and rate were measured for various reader transmission power levels. The results show that the location tracking is more precise when the reader transmission power is reduced; however, tag recognition rates also decrease. Therefore, it is necessary to adjust the reader transmission power accordingly when using RFID to track machines in an actual underground mine. The indoor simulation test methods used in this research should be useful for this process.